WRANGLESTONE - Charlton, Darren (London : Stripes, 2020)
The islands of Lake Wranglestone are a safe haven in a world filled with the Restless Dead. But as the lake freezes over, there's nothing to stop them from crossing the ice. Peter has never really felt at home in a place where practicality and grit are valued above all else. He's nothing like Cooper -- the boy he's always watched from afar. But when he is ordered to join Cooper out on the mainland, they find more than just each other. There they unearth a dark secret about Wranglestone's past. One that forces the pair to question everything they've ever known.
Short-listed for Costa Book Award 2020 (UK).
Keywords: Zombies -- Fiction; Survival -- Fiction; Secrecy -- Fiction; Horror fiction